Serological Diagnosis of Bovine Brucellosis in the Southern Region of the Republic Of Benin - ANAGONOU, SESSIWEDE INGRID NADINE; ANAGONOU, Nadine; Daga, Florian Dadjo; ANAGONOU, Nadine; ANAGONOU, Nadine (My University, 2019)
Brucellosis is a chronic disease common to both humans and animals caused by bacteria of the genus Brucella. The damage caused by brucellosis is aggravated by the disease of humans that often leads to disability and sometimes even life. Our study focused on the serological diagnosis of the disease in cattle on private farms (in Abomey and Zogbodomey) and public in Samiondji in Benin. In fact, 444 cattle were examined. The sera collected were subjected to a fast slide agglutination test with Rose Bengal antigen (Rose Bengal), enzyme immunoassay (enzyme-linked-immuno-sorbent-assay ELISA), and milk samples - ring-proofed on milk to determine the prevalence of brucellosis. The results obtained revealed 118, 185 (out of 444 sera) and 49 (out of 115 milk samples) positive cases (prevalence of 26.6, 41.7 and 42.6%) respectively for Rose Bengal, ELISA and the test of the ring on the milk
Keywords: Brucellosis; prevalence; cattle; serological diagnosis; Benin.